Efficacy of ultrasound guided Thoracic Paravertebral block for postoperative analgesia in Patients Undergoing Percutaneous Nephrolithotomy Surgeries (Pain medicine, 2023)
Background: percutaneous nephrolithotomy (PCNL) is a minimally invasive surgery to treat renal stones. Post-operative pain is distressing to the patient due to the injury to the capsule. Efficacy of ultrasound-guided thoracic paravertebral block at multiple level (T9–T10, T10–T11, T11–T12) was evaluated to manage postoperative analgesia in percutaneous nephrolithotomy surgeries.Methodology: a prospective randomized double-blind study of 60 cases of the American Society of Anesthesiologists I–II patients who underwent percutaneous nephrolithotomy were allocated into group P (test) and group N (control). Immediately after surgery, group P were given ultrasound-guided paravertebral block at T9–T10, T10–T11, T11–T12 on operated side using 5 ml of 0.25 % Levobupivacine at each level, while group N did not receive paravertebral block. The patients were assessed for visual analogue scale (VAS), time for first rescue analgesic, number of rescue analgesics in first 24 hrs postoperatively.Results: VAS pain scale shows significant difference between group P (4.2 + 0.8) and group N (5.3 + 1.1) (p < 0.05) at 30 mins, 2, 4, 8 hrs postoperatively. Total opioid consumption at postoperative 2, 6, and 24 hrs was less in group P than group N (P < 0.05). Number of rescue analgesics in first 24 hrs post-surgery in group P was 3.0 ± 0.4, and 4.0 ± 1.1 in group N with statistical significant difference (p = 0.0001). Total dose of opioid consumption (mg) in group P was 110 ± 40.45, and 155 ± 64.87 mg in group N with statistical significant difference (p = 0.002). The group N cases used more opioid than group P, with lower scores for satisfaction (p < 0.05). Analgesic consumption in postoperative 24 hrs of group P was less than that of group N (P = 0.001). Patient satisfaction score was significantly higher in group P than group N (P = 0.0001) in 24 hrs. No nausea and/or vomiting were noted in both groups.Conclusion: ultrasound-guided thoracic paravertebral block had more analgesic, and reduce the requirement of opioids and maintains stable hemodynamics.
Keywords: percutaneous nephrolithotomy; ultrasound-guided paravertebral block; postoperative analgesia; visual analogue scale